Gastrointestinal stromal tumor coexisting with disseminated peritoneal leiomyomatosis - Kenri Akamine; Jun Kadono; Hirofumi Otsuka; Kazuto Ueno; Takeshi Shimizu; Yuki Nagata; Teruhiko Watanabe; Masahiko Osako; Naoki Ishizaki; Mineo Tabata (Surgical Case Reports, 2019)
Abstract Background A case of gastrointestinal stromal tumor (GIST) coexisting with disseminated peritoneal leiomyomatosis (DPL) is rare. We report a case of GIST coexisting with DPL. Case presentation A 50-year-old woman underwent exploratory laparoscopy under a preoperative diagnosis of gastric GIST with an ovarian tumor or peritoneal dissemination in the pelvic space. Laparoscopy showed multiple peritoneal masses in the pelvic space. Intraoperative frozen sectioning of the pelvic tumors showed multiple spindle cells, suggesting leiomyomas or retroperitoneal tumors; however, it was difficult to rule out peritoneal dissemination from GIST. No disseminated lesion was noted near GIST, and hence, we believed that GIST and pelvic lesions had different origins. We achieved R0 resection by partial resection of the stomach, total hysterectomy, and bilateral salpingo-oophorectomy. The postoperative immunohistopathological examination confirmed the final diagnosis of GIST and DPL. The patient has been recurrence free for 10 years. Conclusions Immunohistochemical examination is essential for correct diagnosis for GIST and DPL. R0 curative resection should be scheduled after immunohistochemical examination of specimens obtained from exploratory laparoscopy.